Theater and conflict - Velásquez Ochoa, Farley (Estudios de Filosofía, 2000)
In the twentieth century, many an artist has taken historic events (and sometimes even the nightmares of human history), as a starting point to pose questions about the man of today and the man of the future. This paper explores that topic relating social, politic and human conflicts to the performing arts. It is also thought the use of recreating historical events, topics and characters to promote reflection and strength hope and memory.